2020
DOI: 10.1111/jcmm.15964
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of IRE1/JNK pathway in HK‐2 cells subjected to hypoxia‐reoxygenation attenuates mesangial cells‐derived extracellular matrix production

Abstract: Endoplasmic reticulum (ER) stress and inflammatory responses play active roles in the transition of acute kidney injury (AKI) to chronic kidney disease (CKD). Inositol‐requiring enzyme 1 (IRE1) activates c‐Jun NH2‐terminal kinase (JNK) in ER stress. Tubular epithelial cells (TEC) are the main injury target and source of AKI inflammatory mediators. TEC injury may lead to glomerulosclerosis, however, the underlying mechanism remains unclear. Here, hypoxia/reoxygenation (H/R) HK‐2 cells were used as an AKI model.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 46 publications
1
13
0
Order By: Relevance
“…Moreover, we observed that in I/R-injured heart, c-Jun phosphorylation at both Ser63 and Ser73 was significantly attenuated by the JNK inhibitor whereas inhibition of AP-1 did not modulate the phosphorylation of JNK, which suggested that c-Jun/AP-1 acts downstream of JNK to increase sEH expression in response to the activation of the IRE1α branch of ER stress. The finding of IRE1α-initiated JNK activation was consistent with previous studies [15,16] and elucidation of the c-Jun/AP-1 mediation in IRE1α-driven sEH upregulation furthered our understanding of the role of JNK activation in myocardial I/R injury.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Moreover, we observed that in I/R-injured heart, c-Jun phosphorylation at both Ser63 and Ser73 was significantly attenuated by the JNK inhibitor whereas inhibition of AP-1 did not modulate the phosphorylation of JNK, which suggested that c-Jun/AP-1 acts downstream of JNK to increase sEH expression in response to the activation of the IRE1α branch of ER stress. The finding of IRE1α-initiated JNK activation was consistent with previous studies [15,16] and elucidation of the c-Jun/AP-1 mediation in IRE1α-driven sEH upregulation furthered our understanding of the role of JNK activation in myocardial I/R injury.…”
Section: Discussionsupporting
confidence: 89%
“…The coupling of ER stress to JNK activation was deciphered by the finding of JNK activation by IRE1 [14]. Activation of the IRE1/ JNK pathway mediates the secretion of inflammatory cytokines in tubular epithelial cells subjected to hypoxia-reoxygenation [15] and suppression of IRE1/ JNK signaling contributes to myocardial protection conferred by low-dose lipopolysaccharide during I/R [16].…”
Section: Introductionmentioning
confidence: 99%
“…HK-2 cells were purchased from ATCC (the Global Bioresource Center) and cultured at 37 °C and 5% CO 2 in a humidified incubator with Dulbecco's Modified Eagle Medium (DMEM)/F12 medium (Gibco, Thermo Fisher Scientific, United States), which contains 10% fetal bovine serum (FBS, Gibco), 100 U/mL penicillin, 100 μg/ml streptomycin, and 10% fetal bovine serum (Geneview), 1% non-essential amino acids (M7145, Sigma, Missouri, United States), and 1% glutamine amide (G3126, Sigma). The methods used to establish the H/R injury model are described in detail in our previous study (Liang et al, 2020). Briefly, HK-2 cells with serum-free DMEM/F12 were equilibrated to 37 °C, and subjected to hypoxic conditions of 5% CO 2 , 1% O 2 , and 94% N 2 for 4 h. The cells were harvested at 6, 12, and 24 h after culturing the cells under normal oxygen content conditions of 5% CO 2 and 95% air at 37 °C.…”
Section: Hypoxia/reoxygenation Model Of Hk-2 Cellsmentioning
confidence: 99%
“…AKI is pathologically characterized by sublethal and lethal damage of renal tubules. In our previous study, we reported that the inositol-requiring enzyme 1 (IRE1)/c-Jun NH2-terminal kinase (JNK) pathway in the endoplasmic reticulum (ER) stress is activated in cases of AKI to mediate renal tubules epithelial cell damage incurred from inflammatory reactions (Liang et al, 2020). Renal tubular cell death is an early symptom of AKI, characterized by abnormalities of the ER, mitochondria, and other organelles through the release of chemokines from acutely injured cells that can induce multiple cell death pathways, such as apoptosis and ferroptosis.…”
Section: Introductionmentioning
confidence: 99%
“…Among the cytokines secreted by the kidney, MCP-1 is mainly responsible for leukocyte recruitment, responds to various cytokines, including IL-1α and TNF-α [8,9], and plays an important role in the pathogenesis of different kidney injuries [10]. In human proximal tubular cells HK-2, hypoxia-induced MCP-1 expression is mediated by the c-Jun NH2terminal kinase (JNK) pathway [11]. The p38 pathway is also involved in albumin-induced MCP-1 expression in renal tubular epithelial cells [12].…”
Section: Introductionmentioning
confidence: 99%